2021
DOI: 10.36663/tatefl.v2i2.108
|View full text |Cite
|
Sign up to set email alerts
|

Motivation as Contributing Factor That Impacts Teaching Excellence in Learning

Abstract: Motivation is known as a dynamic and complex thing that provides an important role in learning related to success and failure. There are many factors that greatly influence the quality of teaching motivation. The quality of teaching will be important in the learning process in various ways in education. Education is an important part of the learning process. Commitment and sincerity are things that should be considered in shaping learning patterns to achieve improvement and change. One of the factors that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…(Madiyoh et al, 2018) also stressed that movie is an authentic audio-visual media materials is believed to be motivating, stimulating and facilitating the teaching and learning of foreign language. Motivation plays important roles in language learning process (Dipa, 2021). During the implementation of study, students showed a great enthusiasm and showing high motivation in learning.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…(Madiyoh et al, 2018) also stressed that movie is an authentic audio-visual media materials is believed to be motivating, stimulating and facilitating the teaching and learning of foreign language. Motivation plays important roles in language learning process (Dipa, 2021). During the implementation of study, students showed a great enthusiasm and showing high motivation in learning.…”
Section: Findings and Discussionmentioning
confidence: 99%